2020
DOI: 10.1093/ckj/sfz177
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for non-diabetic renal disease in diabetic patients

Abstract: Background Diabetic patients with kidney disease have a high prevalence of non-diabetic renal disease (NDRD). Renal and patient survival regarding the diagnosis of diabetic nephropathy (DN) or NDRD have not been widely studied. The aim of our study is to evaluate the prevalence of NDRD in patients with diabetes and to determine the capacity of clinical and analytical data in the prediction of NDRD. In addition, we will study renal and patient prognosis according to the renal biopsy findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 44 publications
5
26
3
Order By: Relevance
“…We performed a retrospective, multicenter study including 463 patients to evaluate the association of different KB indications with NDHKD. We found that 40% of patients with T2D who underwent a KB presented NDHKD in our population, in agreement with previously published studies, where nondiabetic kidney disease was reported for 27-76% of patients [9,[23][24][25]. The frequency of NDHKD remained considerable in our study, although we assumed hypertensive nephropathy should not be considered as a nondiabetic kidney disease.…”
Section: Discussion/conclusionsupporting
confidence: 92%
See 3 more Smart Citations
“…We performed a retrospective, multicenter study including 463 patients to evaluate the association of different KB indications with NDHKD. We found that 40% of patients with T2D who underwent a KB presented NDHKD in our population, in agreement with previously published studies, where nondiabetic kidney disease was reported for 27-76% of patients [9,[23][24][25]. The frequency of NDHKD remained considerable in our study, although we assumed hypertensive nephropathy should not be considered as a nondiabetic kidney disease.…”
Section: Discussion/conclusionsupporting
confidence: 92%
“…We also assessed the predictive power of individual atypical features. In apparent contradiction with the results of the KB indications analysis, hematuria, HbA1c below 7%, and duration of diabetes under 5 years were predictive of NDHKD, confirming the results of previous studies [5, 7-9, 17, 18, 24-26, 28-41]. These results might seem at odds with the absence of NDHKD among patients with presence of hematuria and short or unknown duration of diabetes which only comprised patients with stable renal function and proteinuria according to the a priori definition of biopsy indications .…”
Section: Discussion/conclusionsupporting
confidence: 76%
See 2 more Smart Citations
“…[4] It has been reported that up to 40% of patients in early stage of T2D demonstrate some degree of microvascular complication. [5] In addition, a high proportion of patients with diabetes are found to have non-diabetic renal disease (NDRD), being nephroangiosclerosis (NAS) the most frequent cause [6][7] Metabolic changes associated with diabetes lead to glomerular hypertrophy, glomerulosclerosis, and tubulointerstitial in ammation and brosis. [5] In addition, according to various studies, one-third of adults with newly diagnosed diabetes mellitus already have kidney damage, suggesting that IRF may occur in pre-diabetic state.…”
Section: Introductionmentioning
confidence: 99%